Efficacy of Arjun (Terminalia arjuna (Roxb. ex DC.) Wight & Arn.) in Arterial Stiffness: A Case Report - Azra Parveen; Tabassum Latafat; Mursaleen Naseer; Jamal Azmat (Traditional and Integrative Medicine)
Arterial stiffness is a growing epidemic associated with an increased risk of cardiovascular events. Arteriosclerosis means hardening of the arteries. Arterial stiffness or arteriosclerosis is often associated with but is distinct from atherosclerosis. High arterial stiffness is known to be a risk factor, as well as a prognostic marker for cardiovascular disease. Terminalia arjuna (Roxb.) Wight & Arn., an indigenous medicinal plant, has been proven to possess different cardioprotective properties, including positive inotropic, hypolipidemic, coronary vasodilatory, and antioxidant effects. A 40-year-old male presented to the outpatient department of Ajmal Khan Tibbiya College and Hospital in August 2022. The patient was diagnosed case of hypertension and type 2 diabetes mellitus and was taking medicines for the same regularly. His vitals and general physical and systemic examination were within normal limits at the time of interrogation, and all his baseline investigations, except his lipid profile, were within normal limits. The patient was screened for arterial stiffness, for which cardiovascular profile tests were performed on the patient using Diabetes Risk Profiler for the assessment of arterial health analysis, which showed severe arterial stiffness. After 12 weeks of treatment with the decoction of powder of chāl arjun (bark of Terminalia arjuna) 6 g twice daily, arterial health analysis assessment improved to mild arterial stiffness. The probable reason for improvement could be due to the mufattiḥ sudad (deobstruent), muraqqiq-e-dam (blood thinner), and muqawwī-i-qalb (cardiotonic) action of chāl arjun. This case report emphasizes and highlights the effect of Terminalia arjuna on arterial stiffness.